Kisaran Inang Cowpea mild mottle virus dan Respons Varietas Kedelai - Mimi Sutrawati; Sri Hendrastuti Hidayat; Bonny Purnomo Wahyu Soekarno; Ali Nurmansyah; Gede Suastika (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Cowpea mild mottle virus (CPMMV) is one of important virus which infects soybean and become an endemic disease since the first time reported in Java and Sumatra. Research was conducted to study the host range of CPMMV and to evaluate response of new type soybean varieties to CPMMV specific isolate. Host range study of CPMMV CR16 isolate was conducted by sap transmission method to 11 species of indicator plants, whereas evaluation of soybean response involved 10 varieties. The resistance response of soybean variety was based on incubation period, and of either the disease incidence or severity. Virus infection on test plants were confirmed by dot immunobinding assay (DIBA) using specific CPMMV antisera. The CPMMV CR16 isolate was able to infect systemically 8 plant species belongs to Leguminoceae, and Solancaeae; while the virus caused local infection on Amaranthaceae. All plant species infected systemically proved to become sources of inoculum for CPMMV when they used in back inoculation to soybean. Response of soybean varieties to CPMMV CR16 isolate can be categorized into susceptible (Detam 1, Detam 2, Detam 3, Anjasmoro, Wilis), moderated (Detam 4, Malika, Dena 1) and resistant (Argomulyo and Grobogan).